ORGANISASI DAN HUBUNGAN KERJA NELAYAN LUNGKAK TANJUNG LUAR DI LOMBOK TIMUR NTB - Husain, Fadly (Forum Ilmu Sosial, 2010)
Lungkak fi shing community is a type of catcher and hunter fi sh. They use this strategy to get morefi sh. This type is a conventional type of fi shing communities in general. Lungkak Fishermen use a varietyof technology systems to capture and hunt fi sh. As for using various kinds and types of boats and fi shinggear. With this type of fi shing is catching and hunting fi sh Lungkak fi shing communities and organizationscreate a strong working relationship fi shermen to take advantage of marine fi sheries resources. Traditionalsocial organization found in almost the same Lungkak fi shermen fi shing communities in Indonesia thatis familiar with the concept of patron client. In fi shing communities Lungkak known Ponggawe (boss)and Sabi (men / labor). In addition there is also the division of tasks between the owners / bosses andsubordinates. This division of tasks ranging from before the sea or the preparation, execution of fi shingactivities and the activities after the return from the sea. In fi shing communities Lungkak a Ponggaweusually recruit a Sabi because of family relation. A punggawe recruit their own relatives as Sabi. Sharingsystem on the Tanjung Luar Lungkak fi shing communities also called Sadoh. Sadoh is a calculation rulefor the outcome of any fi shermen after fi shing.Key words: Charities, employment, patron-Client